(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
This article reveals and systematizes materials on the stages of development of the history of physical education and their integral connection. The study of the history of the development of physical education has been studied as an important source in the development of the necessary knowledge, skills and competencies provided for in the professional training of future specialists in the field of physical education